Enhanced photon absorption in spiral nanostructured solar cells using layered 2D materials. (3rd August 2015) - Tahersima, Mohammad H; Sorger, Volker J
Abstract: Recent investigations of semiconducting two-dimensional (2D) transition metal dichalcogenides have provided evidence for strong light absorption relative to its thickness attributed to high density of states. Stacking a combination of metallic, insulating, and semiconducting 2D materials enables functional devices with atomic thicknesses. While photovoltaic cells based on 2D materials have been demonstrated, the reported absorption is still just a few percent of the incident light due to their sub-wavelength thickness leading to low cell efficiencies. Here we show that taking advantage of the mechanical flexibility of 2D materials by rolling a molybdenum disulfide (MoS2 )/graphene (Gr)/hexagonal boron nitride stack to a spiral solar cell allows for optical absorption up to 90%. The optical absorption of a 1 μ m long hetero-material spiral cell consisting of the aforementioned hetero stack is about 50% stronger compared to a planar MoS2 cell of the same thickness; although the volumetric absorbing material ratio is only 6%. A core–shell structure exhibits enhanced absorption and pronounced absorption peaks with respect to a spiral structure without metallic contacts. We anticipate these results to provide guidance for photonic structures that take advantage of the unique properties of 2D materials in solar energy conversion applications.